Small vertebrates in the spectacled bear’s diet (Tremarctos ornatus Cuvier, 1825) in the north of Peru - Gonzales, Fiorella N. (2016)
There have been numerous studies about Spectacled bear´s diet, however little is known about the small vertebrates it consumes. This study present nine vertebrate species (seven rodent and two birds) as preys of the Spectacled bear, based on the analysis of six feces collected from two locations Upa (Amazonas) and Lagunas Arreviatadas (Cajamarca) in northern Peru. Six of these records were new food items and a new family Caviidae. Vertebrates were found only in the Upa location. Additionally a sampling of small non flying mammals was conducted in there. Our results suggest that the Spectacled bear would be a generalist species. It prefers plants, however if it finds vertebrates in the environment, it could feed on them.